Assessment of Antimicrobial Effects on Broiler Gut Barrier Through Histopathology and Immunohistochemistry of Tight-Junction Proteins - Cuccato, Matteo; Scaglione, Frine Eleonora; Centelleghe, Cinzia; Divari, Sara; Biolatti, Bartolomeo; Pregel, Paola; Cannizzo, Francesca Tiziana (Frontiers in Veterinary Science, 2022)
In recent years, antimicrobial (AM) use in poultry farming has been attracting attention worldwide mainly due to AM resistance spreading. The role of AM prophylaxis in the modulation of gut microbiota, as well as of gut health, is still not clearly understood. Therefore, this study aimed to investigate the role of different prophylaxis protocols in the modulation of the gut barrier in broilers by applying a histopathological approach. Intestinal tissue samples were collected from a total of 240 male broilers (Ross 306), reared and treated with different AM protocols. Haematoxylin and Eosin (HE) staining and a multiple scoring system were used to evaluate the presence of lesions in ileum, cecum and colon of treated broilers. Moreover, immunohistochemistry (IHC) was performed to assess the expression of claudin-3 and ZO-1 proteins in intestinal tissues. The application of a semi-quantitative scoring system was used in IHC stained samples. HE results revealed that intestinal tissues were mainly characterized by epithelial detachment and fusion of the intestinal villi, but also by the presence of lymphocytic infiltrate in the mucosa and submucosa of AM-treated broilers. However, the IHC approach for the evaluation of claudin-3 and ZO-1 proteins showed that their expression was not affected by the different AM treatments. Nevertheless, the presence of intestinal lesions highlighted by histopathology suggests that AM treatments could harm the gut health of broilers, inducing an inflammatory response and consequent epithelial lesions. In order to clarify the role of AM treatments in the modulation of gut barrier in broilers, further studies are needed.